Antibody mediated targeting of the FGFR1c isoform increases glucose uptake in white and brown adipose tissue in male mice - Lewis, Jo E.; Samms, Ricardo J.; Cooper, Scott; Luckett, Jeni C.; Perkins, Alan C.; Dunbar, James D.; Smith, Dennis P.; Emmerson, Paul J.; Adams, Andrew C.; Ebling, Francis J.P.; Tsintzas, Kostas (Oxford University Press, 2017)
The increased prevalence of obesity and its cardiometabolic implications demonstrates the imperative to identify novel therapeutic targets able to effect meaningful metabolic changes in this population. Antibody-mediated targeting of fibroblast growth factor receptor 1c isoform (FGFR1c) has been shown to ameliorate hyperglycaemia and protect from diet- and genetically-induced obesity in rodents and non-human primates. However, it is currently unknown which tissue(s) contribute to this glucose lowering effect. Thus, to elucidate this effect we treated euglycaemic mice with H7, a monoclonal antibody which selectively targets the FGFR1c isoform, and employed whole body positron emission computed tomography with a glucose tracer (18F-flurodeoxyglucose). Treatment with H7 increased basal glucose uptake in white and brown adipose tissues (WAT and BAT respectively), the brain and liver, but reduced it in the quadricep muscles. Consequentially, blood glucose was significantly reduced in response to treatment. Under insulin-stimulated conditions, the effects of H7 were maintained in WAT, BAT, liver and muscle. Treatment with H7 decreased triglyceride content and increased adipose triglyceride lipase content in white adipose tissue, whilst increasing activation of acetyl coenzyme A carboxylase, suggesting futile cycling of triglycerides, albeit favouring net hydrolysis. We demonstrated, in vitro, this is a direct effect of treatment in adipose tissue as basal cellular respiration and glucose uptake were increased in response to treatment. Taken together, these data suggest that antibody-mediated targeting of FGFR1c exerts its powerful glucose-lowering efficacy primarily due to increased glucose uptake in adipose tissue.